Design of adjustable chip breaker for PCD turning tools. (15th April 2020) - Wu, Maochao; Yu, Aibing; Chen, Qiujie; Wang, Yanlin; Yuan, Jiandong; Sun, Lei; Chi, Jianying
Highlights: An adjustable chip breaker is designed for PCD turning tools. Influence mechanisms of inclination angle and the position parameter of chip breaker on chip curling are obtained. A simple set of equations are derived for designing chip breaker parameters, including inclination angle, position parameter and height. A design method for chip breaker parameters of PCD tool is proposed. Abstract: To obtain better chip breaking effect for most cutting parameters, a chip breaker which position on rake face of tool can be adjusted is designed and analyzed. According to the structure and installation features of the PCD insert, structure of adjustable chip breaker is designed. Through finite element simulation and cutting experiments, the influences of chip breaker parameters on the radius of chip curl curvature were analyzed to determine the parameters of chip breaker. Forces on chips and the chip breaking processes of PCD tool with chip breaker were analyzed. The geometric relationships between chip breaker and chip were established. According to the geometric relationship and the chip breaking criterion, the formulas of three chip breaker parameters were deduced. A design method for chip breaker parameters of PCD tool was proposed. The research results show that the radius of chip curl curvature decreases as the inclination angle increases and decreases as the position parameter decreases. There is a threshold for both inclination angle and the position parameter of the chip breaker, and if the threshold is exceeded, severe noise and chip build-up will occur. If the contact point between the chip and the chip breaker is located in the selected segment of chip, the extrusion force between the chip and the chip breaker will increase as the chip grows, which can cause the chip to crack and break easily. The influence mechanisms of inclination angle and the position parameter of chip breaker on chip curling are obtained. A simple set of equations are derived for designing chip breaker parameters, including inclination angle, position parameter and height. A design method for chip breaker parameters of PCD tool is presented. The application of the chip breaker can expand the chip breaking range of cutting parameters for PCD tools.